Obtención de pasta de cacao de alta calidad en base a la fermentación - Cueva Ramírez, Jonny Estuardo (2009)
In Santa Ines Farm owned by the University of Machala study was to obtain pulp of high quality cocoa from the fermentation with the national variety, which has the following objectives: 1. Establish a method for controlled fermentation of cocoa beans National 2. Determine the best treatment in addition to the microorganism involved in the fermentation process leading to obtaining better profit and pulp of high quality cocoa, 3. Disseminate the results in the cocoa producing areas of the catchment area of this research. The fermentation was carried out in fermenters drawers, adding substance to facilitate the process, such as; guarapo cane, yogurt and yeast bread, the variables were analyzed: time of fermentation, acidity of the substrate, temperature, quality of the almonds and quality of fermented pasta. The variance analysis of the records of the fermentation temperature and acidity of the beans for profit, did not give significant results for treatment, because the fermentation process is associated with aerobic metabolism of carbohydrates and other compounds layer of almonds harvested mucilages, which generates energy release that is manifested by the warming of the almonds. The temperature rose to 41 º C in the range of 124 to 148 hours. The level of acidity also fell to between 3.81 to 4.07 pH units. The characteristics of the beans at the end of fermentation, significant differences between treatments with respect to floral aroma, fruity, cocoa, almond, bitter, sour, bitter and astringent. The floral scent in the control, yeast and handsome cane was weak and lacking in almonds treated with yogurt, similar results were recorded for fruit flavors, acidity and almond. With regard to cocoa flavor, this was more intense in the witness that treatments with yeast, yogurt and guarapo cane. Almonds treated with yogurt for fermentation had the highest rate for the bitter taste with an average of 3.6 equivalent of medium to strong, as well as the astringent flavor index was 3.8 or stronger for this treatment while the witness, astringency was rated low. Other features aromas and flavors, smoke, mold, chemicals and wood were not presented. In total at least fermented witness was placed in position on the best quality almonds, followed by guarapo and yeast, but the yogurt was placed in the lowest range of quality national bigwigs.